The RAC1 activator Tiam1 regulates centriole duplication through controlling PLK4 levels - Porter, Andrew P. (J Cell Sci, 2021)
Centriole duplication is tightly controlled to maintain correct centriole number through the cell cycle. Key to this is the regulated degradation of PLK4, the master regulator of centriole duplication. Here, we show that the Rac1 guanine nucleotide exchange factor (GEF) Tiam1 localises to centrosomes during S-phase, where it is required for the maintenance of normal centriole number. Depletion of Tiam1 leads to an increase in centrosomal PLK4 and centriole overduplication, whereas overexpression of Tiam1 can restrict centriole overduplication. Ultimately, Tiam1 depletion leads to lagging chromosomes at anaphase and aneuploidy, which are potential drivers of malignant progression. The effects of Tiam1 depletion on centrosomal PLK4 levels and centriole overduplication can be rescued by re-expression of both wild-type Tiam1 and catalytically inactive (GEF*) Tiam1, but not by Tiam1 mutants unable to bind to the F-box protein βTRCP (also known as F-box/WD repeat-containing protein 1A) implying that Tiam1 regulates PLK4 levels through promoting βTRCP-mediated degradation independently of Rac1 activation.